Food safety knowledge, attitude, and practices (KAP) of Filipino rice cake (FRC) street vendors in Cainta, Rizal - Lamela, Andrei M. (College of Home Economiics, University of the Philippines Diliman, 2024)
While street-vended Filipino rice cakes (FRC) provide food and livelihood for many Filipinos, there are still existing food safety risks that need to be addressed to prevent cases of food-borne illnesses. To provide information on FRC street vending, this study investigated the food safety knowledge, attitude, and practices (KAP) of FRC street vendors in Cainta, Rizal. Specifically, the study (a) measured their KAP levels through a survey and (b) compared their self-reported and observed food safety practices through observation. The survey questionnaire was administered to 50 respondents at least 18 years old in Cainta, Rizal. Food safety practices were observed for 15 to 20 min within a day. Results showed that participants had good food safety knowledge (79.70 ± 27.80%) and food safety attitude (75.53 ± 30.23%) based on their mean scores in personal hygiene, contamination, social responsibility, and cleaning utensils. Although they had good self-reported food safety practices (87.25 ± 17.90%), it was contrary to their observed food safety practices as they scored poorly (37.00 ± 28.40%), particularly in waste disposal, personal hygiene, contamination, and cleaning utensils. Fisher’s exact test found that sex, educational level, and monthly income had a significant (p<0.05) positive effect since females, college graduates, and high-income earners had better food safety KAP scores. Overall, the study implied that despite street food vendors’ good knowledge and attitude, improvement is still needed in the actual practice. Key findings from the study could provide ideas for the authorities about possible food safety topics in training and the resources required (e.g., handwashing facilities and waste disposal) for FRC street vendors to improve their food safety practices.